The features of the fatty acid composition of Pyrus L. total lipids are determined by mountain ecosystem conditions - Voronkov, Alexander S (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2021 Elsevier Masson SAS. All rights reserved.